Analysis of a numerical simulation method of fully grouted and anti-seismic support bolts in underground geotechnical engineering. (June 2016) - Zhou, Hao; Xiao, Ming; Chen, Juntao
Abstract: Numerical simulation method of anchor bolts is a key issue for studying the working mechanism of anchor bolts and their anti-seismic support effect on surrounding rock in an underground cavern. Based on the neutral point theory, a mechanical model of joint action between fully grouted bolts and surrounding rock under seismic loading was built. A new numerical simulation method for the fully grouted bolt, considering the multiple yield failure conditions of the anchoring element, was also proposed. And the numerical simulation method was validated by comparing a simple static laboratory pull-out test of grouted bolts. Then by using the new simulation method, a dynamic time-history analysis case study of underground caverns was conducted. The results indicated that the mechanical model of bolt may reflect the stress characteristics of bolts during an earthquake. Furthermore, the bolts could effectively limit the damage zone and the deformation of surrounding rock. Optimum support parameters existed for bolts in underground caverns under seismic loading, and the local optimum support parameters were slightly different in different parts of the underground caverns.